Hydrogen Peroxide Electroreduction at a Silver-Nanoparticle Array: Investigating Nanoparticle Size and Coverage Effects - Campbell, F; Belding, SR; Baron, R; Xiao, L; Compton, R (2009)
The cathodic reduction of hydrogen peroxide displays altered electrochemical behavior between silver macro- and nanoscale electrodes. In acidic media, two parallel reduction mechanisms have been reported: "normal" and "autocatalytic". The reduction potentials are reported in the literature versus mercury/mercurous sulfate reference electrode. The "normal" reduction of H 2O2, in the presence of H+, forms water and the intermediate OH(ads), taking place at <-0.4 V. The presence of the OH(ads) allows the " autocatalytic" process to proceed at a higher rate, operating at a smaller potential of -0.1 V. We report that "autocatalysis" is absent at a silver nanoparticle (NP)-modified electrode. Moreover, experimentally obtained voltammetry at silver nanoparticle (AgNP)-modified basal plane pyrolytic graphite electrodes, for the "normal" H2O2 reduction, demonstrates a negative peak shift for decreasing NP size as well as a positive peak shift for increased surface coverage. Several factors are involved in this complex behavior, including size effects, mass transport, and possible catalysis. Mass transport models are developed to separate size-related diffusional effects from other possible influences. It is shown that, for electrochemically irreversible reduction processes and widely separated nanoparticles, the voltammetric peak potential (or half-wave potential) varies logarithmically with the radius of the NPs, assumed hemispherical or disk-shaped. In particular, the unusually large overpotential on the NP-modified electrodes as compared to the bulk electrode is seen to result from the enhanced mass transport overpotentials for nanoelectrodes as compared to bulk electrodes. © 2009 American Chemical Society.